The Effectiveness of Using Kahoot App in Improving Reading Comprehension of the Second Grade Students in MTsN 1 Makassar - Hasanah, Inaya; Tahir, Muh.; Talib, Ahmad (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This study aimed to find out the effectiveness of applying Kahoot app in improving reading comprehension of students in MTsN 1 Makassar which focused on Narrative text material. This type of research is pre-experimental research using one-group pretest and posttest design. The sample of this study was 26 students of class VIII at MTsN 1 Makassar. The instrument of data collection for this research was a reading test consisting of pretest and posttest in the form of multiple choice and true/false. The data analysis method used is descriptive analysis and inferential analysis using the Independent Sample t-Test which are processed using SPSS 29.0. The research findings indicated that the second-grade students of MTsN 1 Makassar were pretty low in reading skill. The purpose of this study is to determine the efficacy of using the Kahoot app to improve reading comprehension of students in MTsN 1 Makassar who had been studying Narrative text material. This is a pre-experimental study that employs a one-group pretest and posttest design. The study's sample consisted of 26 eighth-grade students from MTsN 1 Makassar. For this study, a reading test with multiple choice and true/false questions was used to obtain data. The descriptive and inferential data analysis methods employed are descriptive analysis and inferential analysis utilizing the Independent Sample t-Test, both of which are performed using SPSS 29.0. The study showed that the reading proficiency of the MTsN 1 Makassar second grade kids was quite low, but their reading comprehension improved quite significant after the treatment. It was demonstrated by the results of the pre-test mean score of 65.35, which was classified as moderate, and the post-test mean score of 88.65, which was classified as excellent, with an average N-Gain value of 0.71, indicating an improvement. Given that the t-test value was less than 0.05 (0.001<0.005), the alternative hypothesis (H1) was accepted and the null hypothesis (H0) was rejected. As a result, it appears that the use of the Kahoot app is helpful in improving students' reading comprehension at MTsN 1 Makassar. It is expected that Kahoot app can be a recommendation for teachers to improve the teaching performance and enhance the student’s reading comprehension.